Interactions of the transposase with the ends of Mu: formation of specific nucleoprotein structures and non-cooperative binding of the transposase to its binding sites. - Groenen, M A (1987)
Transposition of the E. coli bacteriophage Mu requires the phage encoded A and B proteins, the host protein HU and the host replication proteins. The ends of the genome of the phage, on which some of these proteins act, both contain three transposase (A) binding sites. The organization of these binding sites on each end, however, is different. Here we show, using DNase footprinting experiments with purified A protein, that mutant A binding sites, which affect transposition, have decreased affinity for the transposase. Furthermore the transposase binds non-cooperatively to all A binding sites both in the left and right end of Mu. Electron microscopic studies show that the A protein forms specific nucleoprotein structures upon binding to the ends of Mu. The A and B proteins interact with the ends of Mu to generate larger structures than with the A protein alone.